Death and Disposal Locations of Serial Homicides: The Effect on Recovery Timeframes - Chapman, Brendan (Homicide studies, 2022)
Many factors affect the solvability of homicides, including body disposal location and time between death and recovery. The aim of this exploratory study was to probe a number of spatiotemporal variables for trends across a subset of solved homicide case data from 54 North American serial killers, active between 1920 and 2016 (125 solved cases) to identify areas for further research. We investigated murder site and body disposal site as location variables with eight subcategories across eight discrete time series, seeking insight into how these factors may affect the early stages of an investigation and (therefore by inference) solvability. The findings showed that bodies recovered after 48 hours are more likely discovered outdoor while those discovered within 24 hours, within the victim’s residence. This has implications for the ability to recover forensic evidence when bodes are located after a prolonged time since death as well as in more hostile environments.